ANALISIS RELEVANSI NILAI INFORMASI AKUNTANSI DAN ASIMETRI INFORMASI SEBELUM DAN SESUDAH KONVERGENSI IFRS PADA PERUSAHAAN LQ-45 - Salim, Meliawati; Hariyanto, Simon; Dwijayanti, Patricia Febrina (Widya Mandala Surabaya Catholic University, 2017)
The Financial Accounting Standards in Indonesia has referred to IFRS. The principles of IFRS which are fair value and full dis-closure are expected to generate a certain quality of accounting information. Fair value is market-based measured while full dis-closure is explaning about disclosing all the information which are important in decision making. One of the issue caused by in-formation asymmetry is agency conflict where agent acts for his own behalf because he knows much more information rather than principal about company condition, so as the information is not relevant to be used as the source of decision making. There-fore, the aim of this study is to analyse whether the convergence of IFRS can increase the value relevance of accounting infor-mation and decrease the information asymmetry. The research design is descriptive. The object of the research are the compa-nies which are listed as LQ-45 in 2010-2014 (2012 as cutoff) with 45 companies selected by purposive sampling technique. Technique of data analysis which are used are multiple linier regression and paired t test samples. The results showed that there are increasing of value relevance of accounting information and signicicantly decreasing of the information asymmetry after IFRS convergence in Indonesia.